Comparison Of The Effect Of Vitamin E And Rosmarinic Acid On Expression Of P65 NF-KB Subunit In Diabetes Rat - Wahyu Prima; Nur Samsu; Husnul Khotimah (Faculty of Medicine, University of Jember, 2020)
One of the causes of diabetic nephropathy (ND) that have important role is the increase of free radicals due to high levels of glucose which causes oxidative stress. Oxidative stress activates Angiotensin II and the transcription factor of Nuclear Factor kappa B (NFKb). Prevention and slowing down of ND progression is by using antioxidants. The example of antioxidants are Vitamin E and Rosmarinic Acid (RA). Vitamin E is a conventional antioxidant while RA is a potent antioxidant that also has anti-inflammatory effects. This laboratory experimental study aimed to compare the effects of Vitamin E and RA on the expression of NFKb p-65 in glomelurus of type 2 diabetes rats. NFKb expression of p-65 of positive control increased significantly compared to negative controls (p <0.001), Vitamin E and RA were able to reduce NFKb expression compared to positive controls (p = 0.022 and p = 0.001). respectively there was no significant difference between NFKb expression in the Vitamin E group and Rosmarinic acid but RA decreased better than Vitamin E. It can be concluded that AR had a better effect compared to Vitamin E on the decrease in NFKb p-65 expression in glomelurus type 2 diabetes rats. Keyword: Diabetic nephropathy, Nuclear Factor kappa B (NF-Kb), Rosmarinic Acid, Vitamin E